1982
DOI: 10.1039/p19820001419
|View full text |Cite
|
Sign up to set email alerts
|

Addition reactions of aminium radicals: oxidative and non-oxidative photoaddition of nitrosoamines to non-conjugated polyenes

Abstract: The oxidative photoaddition of N-nitrosodimethylamine to various olefins gives products similar to those obtained from N-nitrodimethylamine despite certain dis-similarity in the mechanisms. The oxidative photoaddition to rrans,rrans,rrans-cyclododeca-1,5,9-triene in the presence of an excess of N-nitrosodimethylamine apparently gave good yields of the expected amino-nitrates. These were reduced by lithium aluminium hydride to afford predominantly the open-chain a,o-substituted amino-alcohol. The non-oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Although fewer investigations have focused on neutral conditions, the photochemical reactions of N -nitrosamines in acidic conditions were extensively explored by Chow and co-workers in the late 1960s through the 1980s. ,, Many of these reactions have been reviewed previously, , but are covered briefly here for completeness. Chow and co-workers found that the reactions of nitrosamines under photolytic conditions with various substrates are dominated by the reactivity of the produced aminium radical, and consequently require acidic conditions .…”
Section: Photochemistrymentioning
confidence: 99%
“…Although fewer investigations have focused on neutral conditions, the photochemical reactions of N -nitrosamines in acidic conditions were extensively explored by Chow and co-workers in the late 1960s through the 1980s. ,, Many of these reactions have been reviewed previously, , but are covered briefly here for completeness. Chow and co-workers found that the reactions of nitrosamines under photolytic conditions with various substrates are dominated by the reactivity of the produced aminium radical, and consequently require acidic conditions .…”
Section: Photochemistrymentioning
confidence: 99%